Influence of Dialect and Stimulus Audibility on LiSN-S Performances - Skinner, Julia M (East Carolina University, 2018)
The main objectives were to investigate the effect of dialect on Listening in Spatialized Noise-Sentences (LISN-S) performances and to assess the relationship between bilateral pure-tone threshold averages (PTAs) and LISN-S performances. Participants were young adults with normal audiograms with self-identified American Southern or non-Southern dialects. No significant LiSN-S threshold differences were found between dialect groups. The strongest significant correlations were found between PTAs and the LiSN-S +/-90° conditions.
Keywords: audiology; dialect; diagnostics; research; speech recognition